Digitalis therapy is associated with higher comorbidities and poorer prognosis in patients undergoing ablation of atrial arrhythmias: data from the German Ablation Registry - Frommeyer, Gerrit; Brachmann, Johannes; Ince, Hüseyin; Spitzer, Stefan G.; Thomas, Dierk; Willems, Stephan; Schumacher, Burghard; Schirdewahn, Petra; Lewalter, Thorsten; Hochadel, Matthias; Senges, Jochen; Eckardt, Lars (Clinical research in cardiology, 2019)
BACKGROUND: Digitalis glycosides are employed for rate control of atrial fibrillation. Recent studies suggested potential harmful effects of digitalis monotherapy and combination with antiarrhythmic drugs. The aim of the present study was to assess the prevalence and potential impact of digitalis therapy on outcome in patients undergoing catheter ablation of supraventricular arrhythmias. - METHODS AND RESULTS: The German Ablation Registry is a nationwide, prospective registry with a 1-year follow-up investigating 12,566 patients receiving catheter ablations of supraventricular arrhythmias in 52 German centres. The present analysis focussed on pharmacotherapy in 8608 patients undergoing catheter ablation of atrial tachycardia, atrial fibrillation, or atrial flutter. Patients receiving digitalis therapy (n = 417) were older and presented a significantly increased prevalence of comorbidities including coronary artery disease, heart failure, diabetes, and pulmonary disease. One-year mortality was significantly higher in digitalis-treated patients (4.7% vs. 1.3%, p < 0.001), most strikingly in patients undergoing ablation of atrial flutter. This effect was maintained after adjustment for important risk factors. Similar results were obtained for as the combined endpoint of death, myocardial infarction, stroke and major bleeding (6.6% vs. 2.7%, p < 0.001), and non-fatal rehospitalisations (54.1% vs. 45.1%, p = 0.001). - CONCLUSION: In the present study of patients undergoing catheter ablation of supraventricular arrhythmias, an association of digitalis therapy with increased mortality and an increased rate of other severe adverse events were observed. The results from this 'real-life' registry are consistent with previously published studies. However, whether digitalis therapy promotes a poorer prognosis or may just serve as a marker for this aspect cannot be thoroughly interpreted.